Reliability and validity of daily physical activity measures during inpatient spinal cord injury rehabilitation. (30th August 2016) - Zbogar, Dominik; Eng, Janice J; Miller, William C; Krassioukov, Andrei V; Verrier, Mary C
Objectives: To assess the test–retest reliability and convergent validity of daily physical activity measures during inpatient spinal cord injury rehabilitation. Design: Observational study. Setting: Two inpatient spinal cord injury rehabilitation centres. Subjects: Participants ( n  = 106) were recruited from consecutive admissions to rehabilitation. Methods: Physical activity during inpatient spinal cord injury rehabilitation stay was recorded on two days via (1) wrist accelerometer, (2) hip accelerometer if ambulatory, and (3) self-report (Physical Activity Recall Assessment for People with Spinal Cord Injury questionnaire). Spearman's correlations and Bland–Altman plots were utilized for test–retest reliability. Correlations between physical activity measures and clinical measures (functional independence, hand function, and ambulation) were performed. Results: Correlations for physical activity measures between Day 1 and Day 2 were moderate to high (ρ = 0.53–0.89). Bland–Altman plots showed minimal bias and more within-subject differences in more active individuals and wide limits of agreement. None of these three physical activity measures correlated with one another. A moderate correlation was found between wrist accelerometry counts and grip strength (ρ = 0.58) and between step counts and measures of ambulation (ρ = 0.62). Functional independence was related to wrist accelerometry (ρ = 0.70) and step counts (ρ = 0.56), but not with self-report. Conclusion: The test–retest reliability and convergent validity of the instrumented measures suggest that wrist and hip accelerometers are appropriate tools for use in research studies of daily physical activity in the spinal cord injury rehabilitation setting but are too variable for individual use.